Transformative Leadership, Locus Of Control On Fraud Detection And Environmental Performance - Agus Bandiyono (Jurnal Akuntansi, 2022)
This study aims to determine the effect of transformative leadership, and locus of control on fraud detection with environmental performance as a moderating variable. This research was conducted by the government agency XYZ with a sample of 40 respondents. The data comes from a questionnaire that is filled in by the respondent. The results of this study are transformational leadership has a positive effect on fraud detection, locus of control has a positive effect on fraud detection, the environmental performance has a positive effect on fraud detection, and environmental performance can strengthen the influence of transformational leadership on fraud detection, and environmental performance can strengthen the influence of locus of control on fraud detection.